2017
DOI: 10.1515/slgr-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning Methods in Continuing Education of Paramedics

Abstract: Abstract. The process of continuing education of paramedics is based on gaining educational credits during five-year educational periods. One of the forms of self-improvement are Internet-based educational programs. The lack of regulations concerning the organizational and technical aspects of e-learning made the authors attempt to analyze the phenomenon. The aim of the article is to present an initial analysis of the role of online educational programs in comparison with other forms of professional training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The results obtained suggest that the occupational group most resistant to stress is that of paramedics. The explanation can be found in research on the professional qualifications of paramedics which show that this is a young occupational group characterized by a high level of responsibility, satisfaction, benefiting from modern lifelong learning, confidence in the tasks performed and motivation to act, although they do feel tired at work and have the impression that doctors and nurses do not have enough confidence in them [17,18,19]. However, as other studies show, the profession of paramedic is highly at risk for depression or sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained suggest that the occupational group most resistant to stress is that of paramedics. The explanation can be found in research on the professional qualifications of paramedics which show that this is a young occupational group characterized by a high level of responsibility, satisfaction, benefiting from modern lifelong learning, confidence in the tasks performed and motivation to act, although they do feel tired at work and have the impression that doctors and nurses do not have enough confidence in them [17,18,19]. However, as other studies show, the profession of paramedic is highly at risk for depression or sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Research into practice and a review of academic publications and textbooks, supported by an in-depth analysis of the materials available on various educational platforms (mainly at the academic level), make it possible to formulate the thesis that no unambiguous definition of the concept of an 'e-textbook' exists (Leszczyński et al, 2017;Ren-Kurc et al, 2013;Walat, 2013). Moreover, there are no basic indications or instructions that publishers should follow.…”
Section: E-textbooks -Definition and Featuresmentioning
confidence: 99%
“…E-textbooks are most often meant for students of emergency medicine (n = 8, 62%), nursing (n = 6, 46%), medicine (n = 4, 31%), as well as public health, physiotherapy, electroradiology, speech therapy, biotechnology, cosmetology, and others. According to the authors, such a high percentage of e-textbooks used to train paramedics in Poland can be explained by their statutory possibility of professional improvement through online educational programmes (Leszczyński et al, 2017;Wejnarski et al, 2018). Subjects taught online or supported by online learning include basic, behavioural, and social sciences, as well as clinical and pre-clinical studies.…”
Section: E-textbooks To Support Polish Medical Educational Institutiomentioning
confidence: 99%
“…The positive outcomes and feedback from students from the use of new technology correlates with Leszczyński et al (2017) study of an emergency medicine DL course. Leszczyński et al (2017) found that students are enthusiastic about the use of modern methods of education, value the substantive quality and innovation presented by these new materials and are quick to adjust to new technologies. The use of immersive technology in education has been found to enrich the skills that students are expected to obtain.…”
Section: Learning Outcomesmentioning
confidence: 83%
“…Distance learners seek to make better use of their time, have geographic independence and also often require a flexible schedule (Rodrigues et al, 2014). Leszczyński et al (2017) details the benefits of DL as time saving and providing access to an extensive variety of learners, flexible learning hours, the prospect of modifying academic content to the individual learner, and decreased education cost in the long run. Markova et al (2017) found that the primary reason that had influenced student's decision to choose DL to be the prospect of being able to combine their studies and 16th International Conference on Cognition and Exploratory Learning in Digital Age (CELDA 2019) employment, followed by the opportunity to study from home, and lastly the flexibility of "school hours".…”
Section: Introductionmentioning
confidence: 99%